Fe-Cr alloy and its manufacturing method
By reducing the donor concentration in the oxide film of Fe-Cr alloys through controlled heating and electrolytic treatment, the method enhances corrosion resistance, addressing the inconsistency in conventional methods and improving pitting corrosion potential.
Patent Information
- Application Number
- JP2021059102
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-31
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2041-03-31
AI Technical Summary
Conventional methods for enhancing the corrosion resistance of Fe-Cr alloys, such as stainless steel, fail to consistently achieve satisfactory corrosion resistance, particularly in harsh environments, despite controlling the surface coating.
The method involves reducing the donor concentration in the oxide film on the surface of the Fe-Cr alloy by increasing the fraction of Fe oxide and Fe hydroxide in the outermost region through a two-step process: heating in a vacuum or reducing atmosphere followed by electrolytic treatment in a neutral aqueous solution, controlling the donor concentration and fraction of Fe oxides/hydroxides to specific ranges.
This approach significantly improves the corrosion resistance of Fe-Cr alloys, particularly against pitting corrosion, by forming a denser oxide film with reduced donor concentration, ensuring excellent corrosion resistance even in corrosive environments.
Smart Images

Figure 0007599364000001 
Figure 0007599364000002 
Figure 0007599364000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an Fe-Cr alloy and a manufacturing method thereof, and more particularly to an Fe-Cr alloy having excellent corrosion resistance and a manufacturing method thereof. [Background technology]
[0002] Fe-Cr alloys, including stainless steel, have excellent corrosion resistance and are widely used as components in corrosive environments such as marine environments and chemical plants. In recent years, the price of rare metals has been rising sharply, and there is a demand for Fe-Cr alloys with reduced alloying and further improved corrosion resistance.
[0003] It is known that the corrosion resistance of Fe-Cr alloys is affected not only by the amount of alloy but also by the surface film, and various stainless steels with improved corrosion resistance from the perspective of surface film control have been investigated.
[0004] Patent Document 1 describes a stainless steel for fuel cells having a coating obtained by subjecting the surface of stainless steel containing 16 mass% or more of Cr to anodic electrolysis in an electrolyte solution containing sodium sulfate, the coating having an intensity ratio [(OO / OH)) / (Cr / Fe)] of 1.0 or more as determined by X-ray photoelectron spectroscopy.
[0005] Patent Document 2 describes a stainless steel with excellent resistance to microbial corrosion, which has a two-layer coating on its surface: an outer layer made of Cr(III)-Fe(III) hydroxide, in which the ratio of the amount of Fe(III) contained in the Fe(III) hydroxide to the total amount of Cr(III) and Fe(III) contained in the hydroxide is 60 atomic % or more, and an inner layer mainly made of Cr(III)-based oxides and / or hydroxides, in which the ratio of the amount of Cr(III) contained in the Cr(III)-based oxides and / or hydroxides to the total amount of Cr(III) and Fe(III) contained in the coating is 60 atomic % or more.
[0006] Patent Document 3 describes a method for forming a protective film for inhibiting corrosion on a metal surface by treating the metal in high-temperature water of 150°C or higher, in which a protective film formation process is carried out using a plurality of samples, each with a different treatment time, the capacitance of each of the protective films formed is detected, the capacitance of each sample is compared to detect the point at which the capacitance rises again from the minimum value or a point near this point, the treatment time is regarded as the optimal immersion treatment time for the treatment liquid and treatment conditions at that time, and the protective film formation process under those conditions is terminated. [Prior art documents] [Patent documents]
[0007] [Patent Document 1] JP 2011-47041 A [Patent Document 2] Japanese Patent Application Publication No. 7-26395 [Patent Document 3] Special Publication No. 5-70715 [Non-patent literature]
[0008] [Non-Patent Document 1] S. Tanuma, CJ Powell and DRPenn: Surf. and Interface Anal., VOL. 11 (1988). p. 577-589 Summary of the Invention [Problem to be solved by the invention]
[0009] However, even when a surface coating satisfying the strength ratio as described in Patent Document 1 is formed, there are cases where the obtained corrosion resistance varies. Similarly, in Patent Document 2, there are cases where satisfactory corrosion resistance cannot be ensured even when the coating composition is controlled. Furthermore, the metal having a protective coating obtained by the formation method described in Patent Document 3 also fails to ensure satisfactory corrosion resistance.
[0010] Thus, with conventional techniques, it has been difficult to ensure adequate corrosion resistance even when the surface coating of Fe-Cr alloys such as stainless steels is controlled.
[0011] The present invention has been made to solve these problems, and an object of the present invention is to provide an Fe-Cr alloy that can exhibit excellent corrosion resistance even in a corrosive environment without impairing the corrosion resistance of the Fe-Cr alloy, and a method for producing the same. [Means for solving the problem]
[0012] As a result of extensive research aimed at solving the above problems, the inventors have discovered that the corrosion resistance of an oxide film formed on the surface of an Fe-Cr alloy can be significantly improved by reducing the donor concentration in the oxide film and increasing the proportion of Fe oxide and Fe hydroxide in the outermost surface region of the oxide film.
[0013] The present invention has been made based on this finding, and the gist of the present invention is as follows.
[0014] (1) An Fe-Cr alloy containing 5.00 to 30.00 mass% Cr and having an oxide film having a thickness of t on the surface thereof, Fe2p 3 / 2 The fraction f of Fe oxide and Fe hydroxide relative to the total amount (atomic %) of oxides and hydroxides in the oxide film when X-ray photoelectron spectroscopy is performed at a take-off angle such that the photoelectron information depth is t / 2 or less from the outermost surface of the oxide film. s Fe is 0.70 or more, Calculated from impedance measurements at 30℃ using a 0.1 mol / L Na2SO4 aqueous solution as the electrolyte. In the oxide film Donor concentration is 5.0 x 10 20 / cm 3 An Fe-Cr alloy, (2) a first step of heating the pickled Fe-Cr alloy at 1000 to 1100°C for 1.0 minute or more in a vacuum or a reducing atmosphere, and then cooling the alloy to 100°C or less; A method for producing an Fe-Cr alloy according to (1), further comprising a second step of performing electrolysis in a neutral aqueous solution having a pH of 4.5 to 7.5 by applying a potential of 0.55 to 0.70 V vs. SHE for 1.0 to 5.0 minutes. Effect of the Invention
[0015] According to the present invention, it is possible to provide an Fe-Cr alloy that exhibits excellent corrosion resistance even in a corrosive environment, and a method for producing the same. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] Hereinafter, one embodiment of the Fe-Cr alloy of the present invention will be described in detail. In this embodiment, the film present on the surface of the base material before the surface treatment described below is referred to as a passive film, and the passive film whose composition has been adjusted by the surface treatment is referred to as an oxide film.
[0017] The present inventors first conducted extensive research into the corrosion resistance of Fe-Cr alloys and the properties of the passive film formed on the steel surface. As a result, they found that the corrosion resistance (pitting potential) of Fe-Cr alloys on which a passive film was formed by pickling was significantly improved by heating the alloy in a vacuum or reducing atmosphere and then electrolytically treating it in a neutral aqueous solution.
[0018] In general, to prevent the occurrence of pitting corrosion, which is one type of localized corrosion, the pitting potential of a material in a given environment, for example, a chloride solution environment, should be set to a potential higher than the corrosion potential (also called natural potential) in the same environment. Fe-Cr alloys, such as stainless steel, are generally known as alloys with excellent corrosion resistance because the passive film formed on their surfaces prevents the corrosion potential from shifting to the noble side to some extent. However, in recent years, there has been a strong demand for Fe-Cr alloys that can exhibit corrosion resistance even in more severe corrosive environments, but in more severe corrosive environments, the passive film alone cannot prevent the corrosion potential from shifting to the noble side and exceeding the pitting potential, which can cause pitting corrosion.
[0019] In such cases, if the amount of alloying elements such as Cr and Mo added is increased, the pitting potential can be shifted further to the noble side, making pitting less likely to occur; however, this results in an increase in manufacturing costs since a large amount of expensive alloying elements is used.
[0020] Therefore, the inventors have conducted extensive research to improve the corrosion resistance of Fe-Cr alloys, and have found that by reducing the donor concentration in the oxide film on the surface of the Fe-Cr alloy and increasing the fraction of Fe oxide and Fe hydroxide in the outermost surface region of the oxide film, it is possible to increase the pitting potential even in a severe corrosive environment such as a chloride solution environment. Furthermore, they have found that such an oxide film can be formed by heating the pickled Fe-Cr alloy in a vacuum or a reducing atmosphere, and then electrolytically treating it in a neutral aqueous solution.
[0021] The oxide film formed on the surface of the Fe-Cr alloy contains Fe-based oxides and hydroxides and Cr-based oxides and hydroxides, and such an oxide film has the properties of a semiconductor. Semiconductors have donors (vacancies) that carry electric current, and the inventors have found that reducing the donor concentration in the oxide film improves corrosion resistance. It is speculated that reducing the donor concentration in the oxide film, i.e., reducing the number of vacancies, reduces the number of defects contained in the oxide film, and improves the protection of the Fe-Cr alloy, especially against chlorides. In addition, it is speculated that increasing the iron concentration in the outermost region of the oxide film makes the outermost region denser, sufficiently reducing the donor concentration, and making it less susceptible to the effects of chlorides.
[0022] The Fe-Cr alloy of this embodiment is based on the above findings. The Fe-Cr alloy and the method for producing the same according to this embodiment will be described in detail below.
[0023] The Fe—Cr alloy according to this embodiment is composed of a base material containing 5.00 to 30.00 mass % of Cr, and an oxide film having a thickness t formed on the surface of the base material. In the oxide film, Fe2p 3 / 2 The fraction f of Fe oxide and Fe hydroxide relative to the total amount (atomic %) of oxides and hydroxides in the film when X-ray photoelectron spectroscopy is performed at a take-off angle where the photoelectron information depth is t / 2 or less from the outermost surface of the film. s Fe is 0.70 or more. In addition, the donor concentration of the oxide film was found to be 5.0×10 20 / cm 3 is less than.
[0024] <Oxide film> In order to increase the pitting potential and improve corrosion resistance, the donor concentration and fraction f s Fe Specifically, while the donor concentration in the entire film is reduced, the amount of Fe in the outermost region is controlled because the corrosion resistance decreases if the amount of Fe oxide or Fe hydroxide in the oxide film on the outermost surface is small.
[0025] The oxide film according to this embodiment has a donor concentration of 5.0×10 determined by impedance measurement at 30° C. using a 0.1 mol / L Na2SO4 aqueous solution as the electrolyte. 20 / cm 3 Less than.
[0026] The oxide film formed on the surface of the base material is mainly composed of Fe-based oxides and hydroxides and Cr-based oxides and hydroxides. In this embodiment, the corrosion resistance is improved by reducing the donor concentration in the entire film. To achieve this effect, the donor concentration must be reduced to 5.0×10 20 / cm 3 More preferably, it is less than 4.0×10 20 / cm 3 or less than 3.0×10 20 / cm 3 The lower limit of the donor concentration is not particularly limited, but for example, 0.01 × 10 20 / cm 3 Above, 0.1×10 20 / cm 3 That's it, 1.0 x 10 20 / cm 3 or more than 1.5×10 20 / cm 3 It may be more than that.
[0027] Here, a method for determining the donor concentration in this embodiment will be described. In this embodiment, impedance measurement is performed using a 0.1 mol / L Na2SO4 aqueous solution at 30° C. as the electrolyte, a Mott-Schottky plot is created based on the measurement results, and the donor concentration is determined from this Mott-Schottky plot.
[0028] More specifically, a metal plate or wire made of the Fe-Cr alloy of this embodiment is cut to an appropriate size as a test piece for measurement, and the oxide film surface is used as the test surface. For example, in the case of a metal plate, a size of 10 mm in length and 10 mm in width is cut. In addition, an aqueous Na2SO4 solution with a concentration of 0.1 mol / L is prepared as the electrolyte. The temperature of the electrolyte is 30°C. Dissolved oxygen in the electrolyte is removed by passing argon or nitrogen through it.
[0029] Additionally, a potentiostat and a frequency response analyzer (FRA) are prepared as measuring equipment. A sine wave is input from the FRA to the potentiostat, which then superimposes the sine wave on a DC voltage and applies it to the test piece. The potentiostat is also configured to send information on the voltage and current of the response signal to the FRA, which then calculates the impedance value.
[0030] An electrochemical cell is then constructed using the above test piece as a working electrode, a platinum electrode as a counter electrode, and a silver-silver chloride electrode as a reference electrode.
[0031] The potential is manipulated using a potentiostat with a potential (E) of 0.80 V as the reference electrode, an amplitude of 0.01 V, and a measurement frequency of f = 1 Hz. The impedance is measured after 30 seconds to determine the capacitance C between the test piece (working electrode) and the counter electrode. The imaginary part of the impedance, Z Im From C=1 / (2πfZ Im) and then calculate the capacitance C by 1 / C 2 (Unit: (F cm -2 ) -2 ) at a potential (E) of 0.80 V. 2 Calculate.
[0032] The same measurement is carried out by changing the potential (E) in 0.05 V increments from 0.80 V to -1.00 V. In this way, the 1 / C 2 Request.
[0033] Next, the electric potential (E) is plotted on the horizontal axis, and 1 / C 2 The measured data is plotted on a coordinate plane with the vertical axis as the Mott-Schottky plot. The slope S of the linear part of the obtained plot is calculated, and the donor concentration N in the oxide film is calculated from the following formula (1). D is determined. In the Mott-Schottky plot of the oxide film according to this embodiment, a straight line portion with a positive slope exists near 0 V, and the slope of this straight line portion is designated as S. The slope S of the straight line portion is determined as the slope of a straight line that connects two points at a 0.05 V pitch and has the maximum slope in the plot from the noble peak to the base peak of the Mott-Schottky plot, and the slope S is determined as the slope of a straight line that is linearly approximated by the least squares method for a total of four plot points including these two points and two points before and after them.
[0034] S = 2 / (qεε0N D ) …(1)
[0035] In the formula (1), ε is the relative dielectric constant of the oxide film, which is set to ε=12 in this embodiment, ε0 is the relative dielectric constant of a vacuum, and q is the elementary charge, which is set to q=1 in this embodiment.
[0036] In this embodiment, Fe2p 3 / 2 The fraction f of Fe oxide and Fe hydroxide relative to the total amount (atomic %) of oxides and hydroxides in the oxide film when X-ray photoelectron spectroscopy is performed at a take-off angle where the photoelectron information depth is t / 2 or less from the outermost surface of the oxide film.s Fe is 0.70 or more. In this embodiment, the region from "the outermost surface of the oxide film to a depth position of t / 2" is defined as the outermost surface region, and the analysis result "when X-ray photoelectron spectroscopy is performed at a take-off angle such that the information depth is equal to or less than a depth position of t / 2 from the outermost surface of the film" corresponds to the analysis result of this outermost surface region.
[0037] The oxide film formed on the surface of the base material is mainly composed of Fe-based oxides and hydroxides and Cr-based oxides and hydroxides. In this embodiment, the corrosion resistance is improved by increasing the generation ratio of Fe oxides and Fe hydroxides in the outermost surface region of the oxide film. In order to achieve this effect, the fraction f S Fe is set to 0.70 or more. More preferably, it may be set to 0.75 or more, 0.80 or more, or 0.82 or more. S Fe Although there is no particular upper limit for the value, excessive increase in the amount of Fe oxide and Fe hydroxide produced may deteriorate the corrosion resistance, so that the value is preferably 0.95 or less or 0.90 or less.
[0038] As described above, in the outermost surface region of the oxide film, the corrosion resistance, particularly the pitting potential, can be improved by increasing the amount of Fe present as an oxide or hydroxide.
[0039] In this embodiment, the thickness of the oxide film is preferably increased from the viewpoint of increasing the pitting potential, and specifically, the thickness t of the oxide film is preferably 1.0 nm or more, more preferably 2.0 nm or more, and further preferably 3.0 nm or more. However, since an excessively large thickness t of the oxide film may result in a decrease in the density of the oxide film, the thickness t of the oxide film is set to 7.0 nm or less, and preferably 5.5 nm or less.
[0040] Here, f S Fe We will explain how to calculate this.
[0041] First, the Fe-Cr alloy after the surface treatment described below is cut into a shape that can fit into the analysis device without processing or chemically treating the surface. For example, a Quantera SXM manufactured by ULVAC-PHI can be used as the analysis device. Next, the cut sample is placed in the analysis device and the oxide film is analyzed by X-ray photoelectron spectroscopy (XPS). The X-ray source is mono-AlKα (hν=1486.6 eV), and the X-ray diameter is set to 200 μm. The analysis is performed on the sample surface without sputtering and without surface treatment.
[0042] In this embodiment, in order to measure the amount of Fe in the outermost surface region of the oxide film, the photoelectron take-off angle is set to Fe2p 3 / 2 The take-off angle is set so that the photoelectron information depth is t / 2 or less from the top surface of the oxide film. The take-off angle is set using the mean free path (λ) of SiO2 as the standard sample, and Fe2p 3 / 2 The information depth (3λ) of photoelectrons was calculated from the following formula (2) (see Non-Patent Document 1).
[0043] λ(SiO2)=0.2(KE) 0.72 ×sinθ(Å) =0.02(KE) 0.72 ×sinθ(nm) (2) Here, KE (kinetic energy) is Fe2p 3 / 2 The KE=776.6eV is used.
[0044] From formula (2), the photoelectron take-off angle according to the information depth to be analyzed is calculated. For example, if the photoelectron take-off angle is 15°, the information depth (3λ) = 1.9 nm, and if it is 90°, the information depth (3λ) = 7.2 nm. Therefore, the photoelectron take-off angle is set according to the thickness of the oxide film, 3 / 2 The photoelectron information depth may be set to be equal to or less than t / 2 depth from the outermost surface of the oxide film.
[0045] From the analysis results, the oxide or hydroxide concentration of each element in the oxide film can be determined by the following method. From the spectrum obtained by XPS, the quantitative values of the elements whose peaks are detected are obtained. Next, the peaks in the metallic state from the base material (base metal) and the peaks in the oxide or hydroxide state are separated, and the ratio of the metallic state to the oxide or hydroxide state of each element is obtained from the ratio of the separated spectra. The oxide or hydroxide concentration (atomic percent) of each element in the oxide film can be obtained by multiplying this ratio of the metallic state to the oxide or hydroxide state by the initial quantitative value.
[0046] The thickness t of the oxide film can be calculated using the following formula (3).
[0047]
number
[0048] Here, t is the thickness of the oxide film, σ is the photoionization cross section of the core electron, n is the number density of atoms, I is the photoelectron intensity, λ is the photoelectron mean free path, θ is the photoelectron take-off angle, and the subscripts o / oxide and m / metal. m = 13.2 Å, λ o = 13.2 Å, n m / n o =2.2.
[0049] <Base material> The Fe-Cr alloy of this embodiment is formed by forming the above-mentioned oxide film on the surface of a base material containing 5.00 to 30.00 mass% Cr, and the base material may be, for example, any of austenitic stainless steel, ferritic stainless steel, martensitic stainless steel, and duplex stainless steel. Since it is necessary to secure a certain amount of Cr in the oxide film as described above, the Cr content of the base material is set to 5.00 mass% or more. On the other hand, if Cr is concentrated in the oxide film, especially in the surface layer of the film, the amount of Fe effective for corrosion resistance cannot be sufficiently secured, making it difficult to form an oxide film within the above range, which may result in deterioration of corrosion resistance, so the Cr content of the base material is set to 30.00 mass% or less.
[0050] The preferred composition of the Fe-Cr alloy base metal is as follows: The composition, in mass percent, is Cr: 5.00-30.00%, C: 0.001-0.100%, Si: 0.005-5.0%, Mn: 0.001-8.00%, Ni: 0.001-40.0%, Mo: 0.001-10.0%, Ti: 0.001-1.0%, Nb: 0.001-1.0%, N: 0.001-0.50%, and the remainder is Fe and impurities.
[0051] In addition, in the composition of the base material, it is preferable that the PREN (Pitting Corrosion Index) is 5.0 to 55.0%. PREN is a type of parameter that indicates pitting corrosion resistance, and is an abbreviation of Pitting Resistance Equivalent Number. PREN is generally used as an index indicating that the larger the PREN value, the higher the pitting corrosion resistance. In this embodiment, it is preferable that the PREN is 5.0 to 55.0% in the composition of the base material. PREN is defined by the following formula (4). The element symbol in the formula indicates the content (mass%) of the element in the steel.
[0052] PREN = Cr + 3.3Mo + 16N (4)
[0053] As described above, the structure of the base metal of the Fe-Cr alloy may be either austenitic or ferritic, but in order to improve the film-forming properties of the oxide film, it is better for the amount of inclusions in the base metal to be low.
[0054] Next, a method for producing the Fe-Cr alloy according to this embodiment will be described. The Fe-Cr alloy of this embodiment is basically manufactured by applying a general process for manufacturing steel. For example, molten steel having a desired chemical composition is produced in an electric furnace such as a vacuum induction melting furnace, and refined in an AOD (Argon Oxygen Decarburization) furnace or a VOD (Vacuum Arc Degassing) furnace. Then, it is made into a steel billet by a continuous casting method or an ingot casting method, and then it is subjected to hot forging, hot rolling, annealing of the hot rolled sheet (solution heat treatment), etc. When manufacturing a thin plate (for example, a steel plate with a thickness of about 3 mm), after the above-mentioned solution heat treatment, it is subjected to cold rolling, and then again to cold rolled sheet annealing (solution heat treatment).
[0055] After annealing the cold-rolled sheet, pickling is performed. Specifically, the annealed sheet is immersed for 15 to 120 seconds in a nitric acid-hydrofluoric acid solution (pickling solution) whose water temperature is 30 to 80° C. and which contains 20 to 120 g / L of nitric acid and 10 to 80 g / L of hydrofluoric acid. As a result, a passive film is formed on the surface of the annealed sheet.
[0056] The Fe-Cr alloy to which the present invention is applicable may be any steel material that has been subjected to pickling after annealing, and is not limited to a plate-shaped steel material, a wire-shaped steel material, a tubular steel material, etc. In the case of a plate-shaped steel material, it may be any of a hot-rolled sheet, a hot-rolled annealed sheet, a cold-rolled sheet, and a cold-rolled annealed sheet.
[0057] Next, a method for controlling the composition of the oxide film will be described. In order to produce an Fe-Cr alloy having an oxide film whose composition satisfies the above range, the following first and second steps are sequentially carried out on the above-mentioned pickled Fe-Cr alloy.
[0058] First step: The pickled Fe-Cr alloy is heated at 1000 to 1100°C for 1.0 minute or more in a vacuum or in a reducing atmosphere, and then cooled to 100°C or lower.
[0059] Second step: The Fe-Cr alloy after the first step is subjected to an electrolytic treatment in a neutral aqueous solution having a pH of 4.5 to 7.5 by applying a potential of 0.55 to 0.70 V vs. SHE for 1.0 to 5.0 minutes.
[0060] In the first treatment, the pickled Fe-Cr alloy is heated in a furnace with a controlled atmosphere. Since the surface of the Fe-Cr alloy is still covered with scale before the pickling treatment, this is removed by the pickling treatment before a new oxide film is formed.
[0061] By carrying out the first treatment, an oxide film mainly composed of Cr-based oxides and hydroxides is formed on the surface of the Fe-Cr alloy. The oxide film formed in the first treatment is dense because it contains a relatively large amount of Cr-based oxides and hydroxides, and the donor concentration is reduced.
[0062] The reason for carrying out the heating in a vacuum or a reducing atmosphere is to prevent the thickness t of the oxide film from growing excessively and to reduce the donor concentration in the oxide film. Examples of the reducing atmosphere include a hydrogen atmosphere and an argon atmosphere. When the atmosphere is made vacuum, the pressure may be, for example, 1 Pa or less. In addition, the pressure may be 10 -3 It may be set to Pa or more.
[0063] The heating temperature is in the range of 1000 to 1100°C. If the heating temperature is less than 1000°C, the oxide film will not be densified and the donor concentration may become high. If the heating temperature exceeds 1100°C, the donor concentration will become high and the oxide film will not be densified. The heating temperature is more preferably 1020 to 1080°C, or 1030 to 1070°C.
[0064] The heating time at 1000 to 1100°C is 1.0 minute or more. If the heating time is less than 1.0 minute, the donor concentration becomes high and the densification of the oxide film does not proceed. If the heating time is too long, the thickness of the oxide film may increase and the donor concentration may increase, so the heating time is more preferably 1.0 to 20.0 minutes, or 2.0 to 15.0 minutes.
[0065] After the heating time at 1000 to 1100°C is completed, the Fe-Cr alloy is cooled to 100°C or less while maintaining the atmosphere, and then removed from the heating furnace. If the Fe-Cr alloy is removed from the heating furnace into the atmosphere while the temperature is above 100°C, the donor concentration of the oxide film may increase, so it is necessary to sufficiently cool the alloy to 100°C or less before removing it from the heating furnace.
[0066] Next, in the second treatment, a potential of 0.55 to 0.70 V vs. SHE is applied for 1.0 to 5.0 minutes in a neutral aqueous solution to perform electrolysis (neutral electrolysis). The oxide film after the first step has a low donor concentration as a whole, but the outermost surface region of the oxide film has low corrosion resistance against the intrusion of chlorides and the like from the outside. Therefore, by performing electrolysis in a potential range of 0.55 to 0.70 V vs. SHE in the second step, Fe-based oxides or hydroxides are formed in the outermost surface region of the oxide film, thereby lowering the donor concentration and densifying the film. This makes it possible to produce an Fe-Cr alloy having an oxide film that satisfies the above range.
[0067] The potential range was set to 0.55 to 0.70 V vs. SHE because the Fe content (f S Fe ) within the above range. If the electrolysis potential is too high, the Cr content in the oxide film is excessively reduced, the donor concentration is increased, and the protective properties of the oxide film are deteriorated. On the other hand, if the electrolysis potential is too low, the Fe content (f s Fe ) sufficiently, which may result in deterioration of corrosion resistance. Therefore, the potential region is set to 0.55 to 0.70 V vs SHE.
[0068] As the neutral aqueous solution having a pH of 4.5 to 7.5, for example, an aqueous sodium nitrate solution, an aqueous sodium chloride solution, ion-exchanged water, tap water, industrial water, natural seawater, etc. may be used.
[0069] In addition, the aqueous solution of the supernatant contained divalent iron ions (Fe 2+ In order to incorporate ferrous sulfate (II) or potassium ferricyanide (II) may be added. 2+ When iron ions (Fe) are included, 2+ ) should be 0.10 mg / L or more. 2+ By including Fe, the production ratio of Fe oxide and Fe hydroxide in the entire oxide film can be increased, and the corrosion resistance can be further improved. 2+ The content of Fe in a neutral aqueous solution is preferably 0.15 mg / L or more. 2+ If the ion concentration is excessively high, there is a risk of reducing the Cr concentration in the oxide film, so it is preferable to keep the concentration at 1.00 mg / L or less.
[0070] The pH of the neutral aqueous solution is 4.5 to 7.5. If the pH is too low, the thickness of the oxide film cannot be sufficiently secured, and the Cr content in the outermost region of the film becomes excessive, resulting in a relatively low Fe content (f S Fe ) decreases, which may deteriorate the corrosion resistance, so the pH is set to 4.5 or higher. It is preferably set to 5.0 or higher. Also, if the pH of the neutral aqueous solution is too high, the Fe content (f S Fe ) may decrease, resulting in deterioration of corrosion resistance, so the pH is set to 7.5 or less, preferably 6.5 or less.
[0071] The treatment temperature in the second step is not particularly limited, but may be within the range of 10.0 to 50.0°C.
[0072] The Fe-Cr alloy according to this embodiment can be produced by the production method described above. EXAMPLES
[0073] Examples of the present invention will be described below, but the present invention is not limited to the conditions used in the following examples. The underlined values in Tables 1A to 3B indicate values outside the range of the present invention.
[0074] Stainless steels having the chemical compositions shown in Tables 1A and 1B were melted in a vacuum induction melting furnace and cast. They were then soaked at 1200°C and hot forged. They were hot rolled to a thickness of 6 mm, and then annealed and pickled. They were then cold rolled to a thickness of 1 mm, and further cold-rolled sheet annealed and pickled in this order. In the pickling after the cold-rolled sheet annealing, the cold-rolled annealed sheet was immersed for 40 seconds in a nitric-hydrofluoric acid solution (pickling solution) containing 60 g / L of nitric acid and 30 g / L of hydrofluoric acid at a water temperature of 60°C.
[0075] After pickling, the obtained cold-rolled steel sheet was subjected to the first step. In the first step, the cold-rolled steel sheet was introduced into a heating furnace with an atmosphere shown in Tables 2A and 2B, and was heated at the annealing temperature shown in Tables 2A and 2B. Furthermore, the cold-rolled steel sheet was allowed to stay in the heating furnace and cooled until it reached the removal temperature shown in Tables 2A and 2B. The pressure when the atmosphere was vacuum was 1 Pa or less.
[0076] Next, in the second step, electrolysis was performed using the neutral aqueous solution shown in Tables 2A and 2B. The electrolysis was performed at a water temperature of 30° C.±2° C. The electrolysis potential and electrolysis time were as shown in Tables 2A and 2B.
[0077] X-ray photoelectron spectroscopy was performed on the oxide film on the surface of the steel sheet after electrolytic treatment. Specifically, the obtained steel sheet was cut into a shape that could fit into the analysis device without undergoing any surface processing or chemical treatment. The analysis device used was a Quantera SXM manufactured by ULVAC-PHI. The cut sample was then placed in the analysis device, and measurements were performed using mono-AlKα (hν=1486.6eV) as the X-ray source with an X-ray diameter of 200μm.
[0078] The "f" in Tables 3A and 3B S Fef is the ratio of the total amount (atomic %) of Fe oxide and Fe hydroxide to the total amount (atomic %) of oxides and hydroxides in the film when analyzed by X-ray photoelectron spectroscopy at the take-off angle (°) at the time of analysis. S Fe The take-off angles (°) shown in Tables 3A and 3B were calculated using the above-mentioned formula (2).
[0079] The thickness t of the oxide film was calculated using the above-mentioned formula (3). In this example, λ m = 13.2 Å, λ o = 13.2 Å, n m / n o =2.2.
[0080] In addition, the donor concentration was measured for the oxide film on the surface of the steel sheet after electrolysis. Specifically, the steel sheet after electrolysis was cut into a size of 10 mm in length and 100 mm in width as a test piece for measurement, and the oxide film surface was used as the test surface. In addition, an aqueous Na2SO4 solution with a concentration of 0.1 mol / L was prepared as the electrolyte. The temperature of the electrolyte was 30°C. Dissolved oxygen in the electrolyte was removed by passing argon or nitrogen through it.
[0081] A potentiostat and a frequency response analyzer (FRA) were prepared as measuring equipment, and a sine wave was input from the FRA to the potentiostat, which then superimposed the sine wave on a DC voltage and applied it to the test piece. The potentiostat was also configured to send the voltage and current information of the response signal to the FRA, which then calculated the impedance value.
[0082] An electrochemical cell was then constructed using the above test piece as a working electrode, a platinum electrode as a counter electrode, and a silver-silver chloride electrode as a reference electrode.
[0083] The potential was manipulated with a potentiostat at a potential (E) of 0.80 V, amplitude of 0.01 V, and measurement frequency f = 1 Hz, based on the reference electrode. The impedance was measured after 30 seconds, and the capacitance C between the test piece (working electrode) and the counter electrode was calculated. The imaginary part of the impedance, Z ImFrom C=1 / (2πfZ Im ) and calculate the capacitance C by the formula, and then divide it by 1 / C 2 (Unit: (F cm -2 ) -2 ) at a potential (E) of 0.80 V. 2 was calculated.
[0084] Similar measurements were performed by changing the potential (E) in 0.05 V increments from 0.80 V to -1.00 V. In this way, the 1 / C 2 asked for.
[0085] Next, the horizontal axis is the potential, and the horizontal axis is 1 / C 2 The measured data was plotted on a coordinate plane with the vertical axis being θ, to obtain a Mott-Schottky plot. The slope S of the linear part of the obtained plot was calculated, and the donor concentration N in the oxide film was calculated from the above formula (1). D was obtained. In the Mott-Schottky plot of the oxide film of this example, a straight line portion with a positive slope was present near 0 V, and the slope of this straight line portion was taken as S. The slope S of the straight line portion was determined by selecting two points connecting two points at a 0.05 V pitch from the noble peak to the base peak of the Mott-Schottky plot, where the slope was maximum, and linearly approximating a total of four plot points, including these two points and two points before and after them, using the least squares method.
[0086] In formula (1), ε is the relative dielectric constant of the oxide film, which is set to ε=12 in this example. ε0 is the relative dielectric constant of a vacuum. q is the elementary charge, which is set to q=1 in this embodiment.
[0087] Next, a pitting potential test was conducted to evaluate the pitting corrosion resistance of the steel sheets after immersion or electrolytic treatment. The test method was specified in JIS G0577, and the test was conducted in 3.5% NaCl at 30°C and 100 A cm -2 The potential above which the pitting potential (V´ c100 The pitting potential of the steel sheet before immersion or electrolytic treatment (pitting potential before treatment V´ c100), and the pitting potential of the steel sheet after immersion or electrolytic treatment (pitting potential after treatment V´ c100 ) are shown in Tables 3A and 3B, respectively. The samples used for measuring the pitting potential were not subjected to any surface processing or chemical treatment, and were used for the measurement in their as-is or as-treated state, without any immediate polishing. The pitting resistance was evaluated by measuring the change in pitting potential V, ΔV', before and after treatment. c100 ("Pitting potential after treatment V' c100 " - "Pitting potential V' before treatment c100 ") exceeding 0.00 V vs. SHE was evaluated as good.
[0088] As is clear from Tables 1A to 3B, all of the steel sheets (invention steels) obtained by the manufacturing method satisfying the present invention have a fraction f of Fe oxide and Fe hydroxide relative to the total amount (atomic %) of oxide and hydroxide in the oxide film. s Fe is 0.70 or more and the donor concentration is 5 × 10 20 / cm 3 Since the thickness was less than 1 mm, excellent pitting corrosion resistance was achieved.
[0089] [Table 1A]
[0090] [Table 1B]
[0091] [Table 2A]
[0092] [Table 2B]
[0093] [Table 3A]
[0094]
Table 3B
Claims
1. An Fe-Cr alloy containing 5.00 to 30.00 mass% Cr and having an oxide film having a thickness of t on a surface thereof, Fe2p 3/2 The fraction f of Fe oxide and Fe hydroxide relative to the total amount (atomic %) of oxides and hydroxides in the oxide film when X-ray photoelectron spectroscopy is performed at a take-off angle such that the photoelectron information depth is equal to or less than t / 2 depth from the outermost surface of the oxide film. s Fe is 0.70 or more, 30°C, 0.1 mol / L Na 2 SO 4 The donor concentration in the oxide film determined by impedance measurement using an aqueous solution as an electrolyte is 5.0×10 20 / cm 3 The Fe-Cr alloy is characterized in that:
2. A first step of heating the pickled Fe-Cr alloy at 1000 to 1100°C for 1.0 minute or more in a vacuum or a reducing atmosphere and then cooling it to 100°C or less; A second step of performing electrolysis in a neutral aqueous solution having a pH of 4.5 to 7.5 by applying a potential of 0.55 to 0.70 V vs. SHE for 1.0 to 5.0 minutes.
Citation Information
Patent Citations
Production of stainless steel spring material
JP1990111900A
Coating composition
JP1993070715A
Stainless steel having excellent microbiological corrosion resistance and its production
JP1995026395A
Ferritic stainless steel improved in corrosion resistance and its production
JP1995216591A
Stainless steel for fuel cell having excellent corrosion resistance and method for producing the same
JP2011047041A
